Trans-Golgi proteins participate in the control of lipid droplet and chylomicron formation. Issue 1 (22nd November 2012) - Hesse, Deike; Jaschke, Alexander; Chung, Bomee; Schürmann, Annette
Abstract : LDs (lipid droplets) carrying TAG (triacylglycerol) and cholesteryl esters are emerging as dynamic cellular organelles that are generated in nearly every cell. They play a key role in lipid and membrane homoeostasis. Abnormal LD dynamics are associated with the pathophysiology of many metabolic diseases, such as obesity, diabetes, atherosclerosis, fatty liver and even cancer. Chylomicrons, stable droplets also consisting of TAG and cholesterol are generated in the intestinal epithelium to transport exogenous (dietary) lipids after meals from the small intestine to tissues for degradation. Defective chylomicron formation is responsible for inherited lipoprotein deficiencies, including abetalipoproteinaemia, hypobetalipoproteinaemia and chylomicron retention disease. These are disorders sharing characteristics such as fat malabsorption, low levels of circulating lipids and fat-soluble vitamins, failure to thrive in early childhood, ataxic neuropathy and visual impairment. Thus understanding the molecular mechanisms governing the dynamics of LDs and chylomicrons, namely, their biogenesis, growth, maintenance and degradation, will not only clarify their molecular role, but might also provide additional indications to treatment of metabolic diseases. In this review, we highlight the role of two small GTPases [ARFRP1 (ADP-ribosylation factor related protein 1) and ARL1 (ADP-ribosylation factor-like 1)] and their downstream targets acting on the trans -Golgi (Golgins and Rab proteins) on LD and chylomicron formation.